Perceptions on awareness, knowledge and confidence in providing information and management of snake-related injuries by medical students in Sarawak, Malaysia - Anisah Frömming, Gabriele Ruth; Rahman, Md Mizanur; Amirul Hakim Jaya,; Esmeralda Mathew,; Mirza, I.; Nur Mahirah, J.; Ahmad Khaldun Ismail, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
The World Health Organization (WHO) has categorised snake-related injuries as a neglected tropical disease which can cause permanent disability, or worse, can lead to death if not treated timely and appropriately. Medical students are exposed to snakebite patients predominantly in their clinical years and depending on the location of their medical postings. This study aimed to determine the perceived awareness, knowledge and confidence level of medical students in providing information and managing snake-related injuries. A quantitative cross-sectional study was designed and the data were collected using a Likert scale questionnaire. The perceived awareness, knowledge and confidence level between pre-clinical and clinical students were tested by an independent sample t-test. A p-value of ≤ .05 was interpreted as statistically significant. Analysis revealed a statistically significant difference of perceived knowledge (p= .009) and perception of confidence level (p= .025) between clinical and pre-clinical students. However, no difference was found in terms of perceived awareness (p> .05). Clinical medical students have a better perception of knowledge and confidence level in providing information and managing snake-related injuries than pre-clinical students. An indepth study on this topic should be conducted to include all medical students in Malaysia. Steps should be taken to improve the knowledge and confidence level of medical students in managing snake-related injuries in Malaysia.